Pengaruh Harga dan Kualitas Produk terhadap Keputusan Pembelinan di Toko Bone Indah, Boswesen Sorong - Timisela, Yanti; Longkutoy, Meytha; Yappens, Bertha (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the impact of price and product quality on purchasing decisions at Toko Bone Indah Boswesen, Sorong, using a quantitative descriptive analysis method. The t-test results indicate that price has a positive and significant effect on purchasing decisions, with tvalue 5.823 > ttable 1.6716 and a significance of 0.000 (< 0.05), confirming hypothesis (H1). Similarly, product quality has a significant effect, with tvalue 3.115 > ttable 1.6716 and a significance of 0.000, confirming hypothesis (H2).The F-test results show an Fvalue of 61.834 with a significance of 0.000 (< 0.05), indicating that price and product quality simultaneously influence purchasing decisions at Toko Bone Indah Boswesen, Sorong.